Complex defects in crystal scintillation materials and phosphors; IOP Conference Series: Materials Science and Engineering; Vol. 168 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2016) - Lisitsyn V. M. Viktor Mikhailovich (The use of radiation-thermal processes in nanotechnology, 2017)
Title screen